Commercial agency and the duty to act in good faith - Tosato, Andrea (Oxford University Press, 2016)
Under Directive 86/653/EEC on the co-ordination of the laws of European Union Member States relating to self-employed commercial agents, commercial agents have an obligation to act ‘dutifully and in good faith’ (the Obligation). This article considers the impact that this general good faith clause has had upon the UK legal order. It first analyses the Obligation, assessing its scope, function and content. It then reviews the choices made by the UK legislature in implementing this duty and scrutinises the manner in which it has been construed and applied by UK courts, as well as commentators. Finally, it charts the areas of the pre-existing common law agency rules that are affected by this imported notion and appraises the resulting alterations to the positive law.